A descriptive study to assess the knowledge of coronavirus among nursing students, Sirmaur, Himachal Pradesh - Sharma, Anjali Devi; Verma, Kavita; Sehgal, Manisha; Verma, Yachna; K., Anupama (International Journal of Research in Medical Sciences, 2020)
Background: The coronavirus disease 2019 (COVID-19) is an emerging infectious disease caused by novel coronavirus and hence this pandemic has a great impact on the education system. Nursing students as part of the health team should know the coronavirus like other communicable diseases. Methods: A quantitative approach and cross-sectional survey research design used to assess the knowledge of Coronavirus among 145 nursing students of district Sirmaur selected through the convenient sampling technique. An online self-structured questionnaire used as a tool for data collection. Descriptive data analysis was done with SPSS (version 23). Results: The result of the study revealed that only 31.7% of students had good knowledge about COVID-19, and 68.3% had average knowledge. Conclusions: There is a need for intervention such as educational programs or pieces of training to educate about the pandemic and its prevention practices to undergraduate students to make our society more secure.